Association between H19 SNP rs217727 and lung cancer risk in a Chinese population: a case control study - Lingling Li; Genyan Guo; Haibo Zhang; Baosen Zhou; Lu Bai; He Chen; Yuxia Zhao; Ying Yan (BMC, 2018)
Abstract Background H19 was the first long non-coding RNA (lncRNA) to be confirmed. Recently, studies have suggested that H19 may participate in lung cancer (LC) development and progression. This study assessed whether single nucleotide polymorphisms (SNPs) in H19 are associated with the risk of LC in a Chinese population. Methods A case-control study was performed, and H19 SNP rs217727 was analyzed in 555 lung cancer patients from two hospitals and 618 healthy controls to test the association between this SNP and the susceptibility to LC. Results The A/A homozygous genotype of rs217727 was significantly associated with an increased LC risk (odds ratio (OR) = 1.661, 95% confidence interval (CI) = 1.155 to 2.388, P = 0.006). Significant associations remained after stratification by smoking status (P < 0.001). Furthermore, the A/A genotype had a higher risk of LC than those of G/G in the squamous cell carcinoma (OR = 2.022, P = 0.004) and adenocarcinoma (OR = 1.606, P = 0.045) subgroups. Conclusions The rs217727 SNP in lncRNA H19 was significantly associated with susceptibility to LC, particularly in squamous cell carcinoma and adenocarcinoma, and identified the homozygous A/A genotype as a risk factor for LC.